Circuit-Level Timing-Error Acceptance for Design of Energy-Efficient DCT/IDCT-Based Systems - Ku He; Gerstlauer, A.; Orshansky, M. (IEEE transactions on circuits and systems for video technology, 2013)
An intrinsic notion of quality floors present in typical digital signal processing circuits can be used to strategically accept some runtime errors in exchange for a reduction in energy consumption. Conventional very large scale integration design strategies do not exploit this degree of error tolerance and aim to guarantee timing correctness, thereby sacrificing energy efficiency. In this paper, we propose techniques for timing error acceptance to improve the quality-energy tradeoff in image and video processing systems under scaled VDD . The basic philosophy is to prevent signal quality from severe degradation, on average, by using data statistics. The introduced innovations include techniques for carefully controlling possible errors and exploiting the specifics of error patterns for low-cost postprocessing to minimize quality degradation. We demonstrate the effectiveness of the proposed techniques on a 2-D inverse discrete cosine transform (IDCT) and a 2-D DCT design. The designs were synthesized using a 45-nm standard cell library, with energy and delay evaluated using NanoSim and VCS. Experiments show that direct applications of controlled error-acceptance techniques allow up to 59% and 71% energy savings by permitting fewer than 1-dB peak signal-to-noise ratio (PSNR) decrease for the 2-D IDCT and DCT designs, respectively. The resulting PSNR remains above 30dB, which is a commonly accepted value for lossy image and video compression. Achieving such energy savings by direct VDD scaling without the proposed transformations results in a 12-dB PSNR loss. The area overhead for the needed control logic is about 4.8% of the original design. To further minimize quality degradation caused by accepted errors in the IDCT, we introduce postfiltering on the output image. The significant improvement of the perceived image quality allows further voltage scaling leading to overall energy savings of 70% for the 2-D IDCT, while costing an additional 1.1% in area.